Mechanical and Structural Properties of Fluorine-Ion-Implanted Boron Suboxide. (23rd January 2012) - Machaka, Ronald; Mwakikunga, Bonex W.; Manikandan, Elayaperumal; Derry, Trevor E.; Sigalas, Iakovos; Herrmann, Mathias
Abstract : Results on a systematic study on the effects of ion implantation on the near-surface mechanical and structural properties of boron suboxide (B6 O) prepared by uniaxial hot pressing are reviewed. 150 keV fluorine ions at fluences of up to 5.0 × 10 16  ions/cm 2 were implanted into the ultrahard ceramic material at room temperature and characterized using Raman spectroscopy, atomic force microscopy, and scanning electron microscopy with energy-dispersive X-ray spectroscopy. Evidence of ion-beam-assisted nucleation of novel clustered B x O y F z particles by ion implantation is revealed. In addition, obtained results also reveal that fluorine implantation into the B6 O specimen leads to an overall degradation of near-surface mechanical properties with increasing fluorine fluence. Implications of these observations in the creation of amorphous near-surface layers by high-dose ion implantation are discussed in this paper.